Training in advanced life support for pediatric nurses - Batalha, Luís Manuel da Cunha (2013)
Training in advanced life support for pediatric nurses Background and AIMS The simulation is an essential part of training in resuscitation and the education of nurses in this area is recent. In the last four years were realized an annual Course of Pediatric Advanced Life Support (CSAVP) for nurses. The aim of this study was to evaluate the opinion that graduates of this course and the level of success in their learning. Methods Descriptive study that involved nurses who attended a CSAVP with duration of 24 hours was held annually between 2009 and 2012. Data were collected at the end of training through an anonymous questionnaire. The opinion of the trainees was assessed for relevance, interest, and distribution of load times for theoretical exposition, workshops and practices and regarding to the organization of the course. The evaluation of learning achievement resulted from the theoretical and practical assessment. Results The success of the learning of the 121 nurses was high. The pass rate was 90% practical and the theoretical test has a median of 85.0% ranging between 68.2% and 93.8%. Most of the nurses considered the teaching methods and evaluation very relevant and interesting. The logistical organization of the course was excellent, with the exception of the material distributed for the study. The distribution of time was adequate, but ¼ of the nurses said that the time of the theoretical exposure was insufficient. Conclusions The survey results show success in the learning and an interesting, relevant and well organized CSAVP. Not only, the study materials must be improved.